On generalized G2-structures and T-duality - del Barco, Viviana Jorgelina (2018)
This is a short note on generalized G2-structures obtained as a consequence of a T-dual construction given in del Barco et al. (2017). Given classical G2-structure on certain seven dimensional manifolds, either closed or co-closed, we obtain integrable generalized G2-structures which are no longer a usual one, and with non-zero three form in general. In particular we obtain manifolds admitting closed generalized G2-structures not admitting closed (usual) G2-structures.